(untitled) (Journal of Dhaka Medical College, 2010)
Poisoning is a common medico-social problem in our country causing around 300,000 episodes and around 2000 death per year. The number of poisoning cases is increasing in our country day by day. The common pattern of poisoning in our country is suicidal, homicidal/criminal and accidental. The incidence, nature, etiology, age group affected and the outcome of poisoning in our country is different from that of the western world. A prospective descriptive study of poisoning cases in Sir Salimullah Medical College and Mitford Hospital was attempted in 2004. Among 100 cases, age of the cases ranged from 15-65 years. Sixty four percent were male. Around 68 percent cases were found businessman, 48% were from low-income group and Fifty three percent cases were educated up to secondary level. Among male patients 57.81% of poisoning caused by suspected sedative poisoning (transport related poison), 28.12% by organophophorous, 3.12% by copper sulphate, 4.98 by benzodiazepines (attempted suicide), 4.98% by Acid and 1.56% by kerosene. Among female patients 41.66% of poisoning caused by organophosphorous compounds, 19.44% by rat killer, 11.11% by copper sulphate, 8.33% by benzodiazepines, 5.55% by acid, 5.55% by savlon, 5.55% by herpic and 2.77% by phenol. Transport related poisoning by short acting sedative-hypnotics for the purpose of hijacking the belongings of the travelers and agrochemicals-organophosphorous compounds for suicidal purpose are the most common poisoning in our country. The pattern and magnitude of poisoning are thus multidimensional and demanding multi-sectoral approach for facing the problem. The comprehensive patient care can improve the poisoning case management in our country. DOI: 10.3329/jdmc.v17i2.6593 J Dhaka Med Coll. 2008; 17(2) : 111-115